PREPARING OF DEMOCRATIC EDUCATION LEADERS IN ISLAMIC EDUCATIONAL LEADERSHIP PERSPECTIVE - Mawardi Lubis (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
The objective of this research was to understand preparing of democratic education leaders in Islamic educa- tion leadership perspective. The approach be used  in research was library  research with a kind of qualitative research. The prosess of gathering data/information was used  review method/technique through references review and  includ- ing social media those connect to preparing democratic education leaders in Islamic education leadership perspective and the analytic technique was descriptive analytic technique. The research result  indicates that preparing democratic education leaders in Islamic education leadership perspective had  to be done the  real actions for students, for every component of educational actvity had to be connected to theoretic and practice Islamic democratic leadership aspect. Keywords: leader, education, democratic, leadership, Islamic